Ulceration of Breast’s Skin due to Topical Corticosteroid Abuse - Berna Aksoy (Journal of Dermatologic Research And Therapy, 2017)
Topical corticosteroids are main therapeutic agents for the treatment of a wide variety of dermatological disorders. Three cases of chronic cutaneous ulceration affecting the skin of the breasts that were caused presumably by previous and continued use of potent topical corticosteroids for the treatment of psoriasis and/or intertrigo lesions were reported here. These three cases were presented to emphasize the potential serious local side effects of topical steroids even progressing to ulceration in breast' skin. These cases highlight the importance of appropriate use of topical corticosteroids, necessity of a strict follow up for adverse effects and the need of warning every patient about possible side effects of topical corticosteroids
Keywords: adverse effect